KOMPETENSI PEDAGOGIK GURU PADA PEMBELAJARAN BACA TULIS AL-QUR’AN DI PONDOK PESANTREN - Daulay, Enris Feyrani; Syaidah, Nur; Ekawati, Erna (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The ability to read and write the Qur’an is a fundamental skill that every Muslim must master, particularly within Islamic educational environments. However, based on observations at Pondok Pesantren TPI Purbasinomba, there are still some students who have not fully acquired proficient Qur’anic literacy skills. This situation demands that teachers possess adequate pedagogical competence in planning, implementing, and evaluating instruction. In addition, the role of the madrasah principal is also crucial in providing guidance and support to foster the professional development of teachers. This study aims to explore the pedagogical competence of teachers and the efforts made to develop it in the teaching of Qur’anic reading and writing. The research employs a descriptive qualitative method through observations and interviews with teachers, the madrasah principal, and students. The findings indicate that teachers’ pedagogical competence is demonstrated through their ability to understand students’ characteristics, design systematic lesson plans, and apply methods such as talaqqi, murojaah, and tilawah tartil during instruction, along with conducting continuous assessments to evaluate student performance. Furthermore, efforts to enhance competence include equivalency programs, participation in seminars and training, involvement in teacher working groups, and other professional development activities. The madrasah principal also plays an active role by providing supervision, motivation, and implementing a system of rewards and punishments. The synergy between teachers and the madrasah principal contributes significantly to improving the quality of Qur’anic literacy instruction. ABSTRAK Baca tulis Al-Qur’an merupakan keterampilan dasar yang wajib dikuasai oleh setiap muslim, terutama di lingkungan pendidikan Islam. Namun, berdasarkan kondisi di Pondok Pesantren TPI Purbasinomba, masih ditemukan sebagian siswa yang belum sepenuhnya menguasai kemampuan baca tulis Al-Qur’an dengan baik. Situasi ini menuntut peran guru agar memiliki kompetensi pedagogik yang memadai dalam merencanakan, melaksanakan, dan mengevaluasi pembelajaran. Selain itu, kepala madrasah turut berperan dalam memberikan pembinaan dan dukungan guna mendorong pengembangan profesionalisme guru. Penelitian ini bertujuan untuk mengetahui kompetensi pedagogik guru serta upaya pengembangannya dalam pembelajaran baca tulis Al-Qur’an. Penelitian ini menggunakan metode kualitatif deskriptif melalui observasi dan wawancara dengan guru, kepala madrasah, dan siswa. Hasil penelitian menunjukkan bahwa kompetensi pedagogik guru sudah tampak melalui kemampuannya memahami karakteristik peserta didik, merancang perencanaan pembelajaran yang sistematis, menggunakan metode talaqqi, murojaah, dan tilawah tartil dalam pelaksanaan pembelajaran, serta melakukan evaluasi berkelanjutan untuk mengukur kemampuan siswa. Selain itu, upaya pengembangan kompetensi dilakukan melalui program penyetaraan, partisipasi dalam seminar dan pelatihan, keterlibatan dalam kelompok kerja guru dan program kegiatan guru. Kepala madrasah juga mendukung dengan memberikan pembinaan, motivasi, serta penerapan reward and punishment. Sinergi antara guru dan kepala madrasah berkontribusi pada peningkatan kualitas pembelajaran baca tulis Al-Qur’an.